MENGAKOMODASI KERAGAMAN SISWA: STRATEGI PEMBELAJARAN SEJARAH BERDIFERENSIASI PRODUK UNTUK MENINGKATKAN MOTIVASI BELAJAR - Utama, Taqwa Ridlo (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The current educational paradigm marks a significant shift with the introduction of the Kurikulum Merdeka, which provides educators with greater freedom to customize lesson plans and evaluations according to the needs and preferences of each student. In this context, the concept of Differentiated Learning becomes a crucial milestone. This research aims to implement and evaluate differentiated product learning strategies to enhance student learning motivation in a classroom setting. The method used is Classroom Action Research (CAR), which involves four stages: planning, implementation, observation, and reflection. Data were collected through observations, document studies, and questionnaires. The results show a significant improvement in student learning motivation. There was a noticeable increase in the